The effects of active lifestyle on metabolic health - Toh, Kenneth You Pan (2015)
The clustering of interrelated risk factors such as, dyslipidemia, hypertension, hyperglycemia and obesity are what contributes to metabolic syndrome (MS) or metabolic disease (MD). MD increases the risk of cardiovascular disease (CVD), type 2 diabetes mellitus (DM). Physical activity (PA) was implemented in several studies and it yield beneficial effects in reducing the risk of MD. PA was quantified into terms of weekly energy expenditure (WEE) and compared against multiple MD indicators, thus relationship between WEE and MD indicators was established. MD indicators that were found to be significant and correlates to WEE: blood glucose concentration (at 1.5 h: p = 0.018; r = 0.552, at 2.0 h: p = 0.001; r = 0.720) and pulse pressure (p = 0.031; r = 0.451). Hence, this is the first study to examine MD indicators in comparison with WEE within the Asian population. The effects of PA on MD indicators can be studied and treatment can implemented on people, suffering from MD or have risk of having MD, as a therapeutic lifestyle changing program.